Pengaruh kualitas pelayanan, promosi, dan harga terhadap kepuasan pelanggan - Nabila, Reza Afra; Rahmi, Palupi Permata (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The development of online business actually opens up promising opportunities for service companies. Therefore, goods delivery services are currently increasing with the existence of online businesses. A well-known freight forwarding and logistics service provider in Indonesia, JNE Agent Dipati Ukur Bandung delivers packages, documents, vehicles and other goods. However, despite previous customer satisfaction surveys, JNE's services, promotions, and prices remain unfavorable to customers. The purpose of the study was to determine the effect of Service Quality, Promotion, and Price on Customer Satisfaction at JNE Dipatiukur. The research method used is quantitative descriptive method. The analysis used includes validity test, reliability test, classical assumption test, multiple regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. Customer satisfaction is descriptively rated as not good, Service Quality is descriptively rated as not good, Promotion is rated as not good and Price is descriptively rated as not good. The results of the analysis show that service quality, promotion, and price have a value that has an influence on customer satisfaction and has a very strong correlation. Simultaneously Service Quality, Promotion and Price affect Customer Satisfaction, have a very strong relationship.